Local anodic oxidation on silicon (100) substrates using atomic force microscopy (2012)
A characterization of local anodic oxidation using scanning probe microscopy is performed on a (100) silicon substrate. The formation of patterns varies as a function of voltage, humidity, and scanning speed. A set of experiments is presented to analyze the voltage and scanning speed dependence under stable environmental conditions (50.5% relative humidity, 22 °C, and 767 mmHg). A finer control of the dimensions of the local oxidation patterns is attained at low voltages and low scanning speeds. Oxide ridges are observed at high voltages independently of the writing speed. Their presence sets up an upper limit for the oxide pattern formation.